A simulation study comparing the Texas two-step and the multistage consecutive fracturing method - Wan Cheng (KeAi Communications Co., Ltd., 2019)
Abstract Multistage hydraulic fracturing in horizontal wells is a critical technique for developing unconventional oil and gas resources. Stress interactions among neighboring fractures cause immature fracture development. The Texas two-step fracturing (TTSF) method is a new technique that aims to enhance fracture complexity and conductivity. This paper compares the fracture development of consecutive fracturing and the TTSF. The fracturing sequence in the multistage fracturing method has a significant effect on the fracture length, fracture width and injection pressure. The consecutive fracturing results in relatively uneven fracture length and width. Certain fractures in consecutive fracturing are restrained to be closed due to the strong stress shadowing effect. In contrast, TTSF has considerable potential for alleviating the negative effects of stress interactions and producing a larger stimulated reservoir volume.